George Washington, young leader - Santrey, Laurence (Mahwah, N.J Troll Associates, 1982)
Traces the life of the first president of the United States from his boyhood at Mount Vernon to his adult years.
Keywords: Washington, George, -- 1732-1799 -- Childhood and youth -- Juvenile literature; Washington, George, -- 1732-1799.; Presidents -- United States -- Biography -- Juvenile literature; Presidents